The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1523/jneurosci.1364-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism of Short-Wavelength Photoreceptors in the Small White Butterfly,Pieris rapae crucivora

Abstract: The eyes of the female small white butterfly, Pieris rapae crucivora, are furnished with three classes of short-wavelength photoreceptors, with sensitivity peaks in the ultraviolet (UV) ( max ϭ 360 nm), violet (V) ( max ϭ 425 nm), and blue (B) ( max ϭ 453 nm) wavelength range. Analyzing the spectral origin of the photoreceptors, we isolated three novel mRNAs encoding opsins corresponding to shortwavelength-absorbing visual pigments. We localized the opsin mRNAs in the retinal tissue and found that each of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(149 citation statements)
references
References 38 publications
(50 reference statements)
7
142
0
Order By: Relevance
“…To our knowledge, no other insects besides pierid and lycaenid butterflies have two blue opsin genes. Our finding of independent duplication events is quite consistent with the very different max values (425·nm and 453·nm) of the pierid blue visual pigments (Arikawa et al, 2005) compared to the lycaenid ( max =437·nm and 500·nm, respectively). Our results also indicate (bootstrap support=100%) that the L. rubidus blue opsin gene duplication event occurred before the radiation of the coppers, hairstreaks and blues.…”
Section: Origins Of a Gene And A Family Of Blue Butterfliessupporting
confidence: 89%
See 4 more Smart Citations
“…To our knowledge, no other insects besides pierid and lycaenid butterflies have two blue opsin genes. Our finding of independent duplication events is quite consistent with the very different max values (425·nm and 453·nm) of the pierid blue visual pigments (Arikawa et al, 2005) compared to the lycaenid ( max =437·nm and 500·nm, respectively). Our results also indicate (bootstrap support=100%) that the L. rubidus blue opsin gene duplication event occurred before the radiation of the coppers, hairstreaks and blues.…”
Section: Origins Of a Gene And A Family Of Blue Butterfliessupporting
confidence: 89%
“…In the case of the small white cabbage butterfly, Pieris rapae (Pieridae) (Arikawa et al, 2005), three short wavelength receptors were found, sensitive to ultraviolet ( max =360·nm), violet ( max =425·nm) and blue ( max =453·nm) light, and each expressing a unique opsin. A spectral filtering pigment was found co-expressed with the blue opsin only in males, producing a uniquely narrow blue receptor, highlighting the changes in the spatial expression patterns of non-opsin filtering pigments as a mechanism for producing a sexually dimorphic retina.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations